Pattern of Microorganisms Isolated from Flame Burn Wounds, and Their Trends of Susceptibility to Antibiotic During Past Three Years - Ehmer Al-Ibran; Sidra Meraj; Mahwish Nasim; Maria Khan; Masood Hussain Rao (Journal of the Dow University of Health Sciences, 2013)
Objective: To determine the prevalent bacteria causing wound infection and their trend of susceptibility to antibiotics over a period of last three years in flame burn cases. This is an observational descriptive study conducted at the Burns Center, Civil Hospital Karachi. Methods: All available wound swabs culture and sensitivity reports of flame burn victims admitted during the period of January 2009 - December 2011 were included. Wound swab was usually taken from the burnt area that appears clinically deep, with pus or with thick eschar. In laboratory, microbial growth on any of the inoculated plates gram staining, biochemical identification and antibiotic sensitivity by disc diffusion method was done.